THU0318 PATTERNS OF CLINICAL PRESENTATION IN TAKAYASU'S ARTERITIS. (2nd June 2020) - Quinn, K. A.; Gribbons, K. B.; Carette, S.; Cuthbertson, D.; Khalidi, N.; Koening, C.; Langford, C.; Mcalear, C.; Monach, P.; Moreland, L.; Pagnoux, C.; Seo, P.; et al.
Abstract : Background: Takayasu's arteritis (TAK) is a clinically heterogenous disease. Patterns of clinical presentation in TAK at diagnosis have not been well described, and a "triphasic pattern" of constitutional symptoms evolving into vascular inflammation and fibrosis has been reported but never systematically evaluated. Objectives: To describe patterns of clinical presentation in TAK at diagnosis and evaluate the presence of an antecedent triphasic disease pattern in patients with TAK who presented with a major ischemic event at diagnosis. Methods: Patients with TAK were prospectively recruited from the National Institutes of Health (NIH) and the Vasculitis Clinical Research Consortium (VCRC). All patients fulfilled the 1990 American College of Rheumatology (ACR) Classification Criteria for TAK. Based on clinical presentation at diagnosis, patients were divided into five groups from the different stages of the triphasic pattern of disease as follows: 1) constitutional symptoms (phase I), 2) carotidynia (phase II), 3) other vascular-associated symptoms (phase II), 4) major ischemic event (phase III) defined as CVA or TIA, retinal ischemia, MI, renovascular hypertension, or mesenteric ischemia, or 5) asymptomatic. Phase II was divided into two separate groups because patients with carotidynia reportedly have a higher rate of relapsing disease. Associated clinical characteristics were evaluated in each group and differences among groups were assessed by chi square test and Kruskal-Wallis test, as appropriate. Preceding symptoms were also assessed to determine the presence of a triphasic disease pattern. Results: A total of 275 patients with TAK were included (VCRC=208; NIH=67). Similar heterogeneity of clinical presentation was identified in each cohort: constitutional symptoms (8%), carotidynia (13-15%), other vascular symptoms (43-47%), major ischemic event (28-30%), and asymptomatic (2-6%). Frequency of male gender was more common in patients who presented with constitutional symptoms or were asymptomatic at diagnosis (p<0.01). Patients who presented with constitutional symptoms and major ischemic events were youngest at diagnosis. Patients in the asymptomatic group were oldest at diagnosis and often were not treated (p<0.01). Involvement of the abdominal vasculature was associated with major ischemic events and asymptomatic presentations. Major ischemic events after diagnosis were infrequent in the groups who did not present with a major ischemic event, occurring in 10-20% cases. Relapse (p<0.01) and recurrent pharyngitis preceding diagnosis (p<0.01) was most frequent in patients who presented with carotidynia. A total of 79 patients [VCRC=59 patients, NIH=20 patients] presented with a major ischemic event. The majority of these patients (53%) reported symptoms of active disease prior to the major ischemic event. Few patients (19%) who presented with a major ischemic event reported a triphasic pattern of disease. Conclusion: There is heterogeneity in clinical presentation at the time of diagnosis in TAK and this heterogeneity can be used to group patients according to pattern of disease presentation. Patients do not necessarily progress sequentially through phases of disease, but the majority of patients presenting with a major ischemic event report some preceding symptoms. Data from this study demonstrate distinct subgroups within TAK and supports the concept that TAK is possibly a heterogenous collection of multiple diseases. References: N/A Disclosure of Interests: None declared